Experimental investigation on surface integrity in machining of Inconel X750 with WEDM using Taguchi technique. (2018) - Kumar, Mandeep; Singh, Hari
The objective of the present work is to investigate the effects of various WEDM process parameters such as pulse on time, pulse off time, servo voltage, peak current, wire tension and wire feed rate on the surface roughness of the machined samples. The analysis of variance was carried out for raw data as well as for signal to noise ratio. Four input parameters have been found to be statistically significant for their effects on the response of interest. The optimum value of surface roughness was obtained at pulse on time - 110; pulse off time - 51; spark gap voltage - 65 V; peak current - 90 A; wire feed - 11; wire tension - 5. The confirmation experiments were also performed for validating the predicted results. Scanning electron microscopy was performed on the machined samples to investigate the effect and microstructure of the samples after machining.